Fabrication of W-Y2O3 composites by ultrasonic spray pyrolysis and spark plasma sintering. (September 2021) - Kim, Jeong Hyun; Ji, Myeongjun; Byun, Jongmin; Jeong, Young-Keun; Oh, Sung-Tag; Lee, Young-In
Abstract: Oxide-dispersion-strengthened tungsten (ODS-W) is the most promising structural materials for military, aerospace and nuclear industries because of their excellent mechanical properties and stability at high temperature. However, conventional mechanical milling methods have reached certain limits in further improving the properties of W and its alloys. In this study, with the aim of synthesizing W based composite powder with homogeneously dispersed yttrium oxide (Y2 O3 ) nanoparticles, a novel process methodology combining ultrasonic spray pyrolysis and subsequent hydrogen reduction has been described. Our results reveal that the W-Y2 O3 composite powders consisted of multiple primary particles of approximately 30 nm with a three-dimensional network and are of high purity. TEM and XPS analysis results demonstrated that Y2 O3 nanoparticles were homogeneously dispersed into the tungsten matrix. In comparison with pure W sintered body, the W-Y2 O3 composite showed a refined grain structure, higher relative density and Vickers hardness, and the combination of an intergranular and a transgranular fracture mode and these were mainly attributed to the homogeneous dispersion of Y2 O3 nanoparticles. Our work shows that ultrasonic spray pyrolysis and subsequent hydrogen reduction is a promising method for preparing high quality ODS-W with high density, fine grains and uniformly dispersed strengthening phase nanoparticles. Highlights: A simple and novel process for ODS-W is demonstrated. The process is based on an ultrasonic spray pyrolysis and subsequent hydrogen reduction. W-Y2 O3 composite powders consisted of multiple primary particles of approximately 30 nm with a three-dimensional network. W-Y2 O3 composite showed the combination of an intergranular and a transgranular fracture mode. W-Y2 O3 composite showed higher relative density and Vickers hardness compared to pure W.